Recombinant Human Perlecan DV and Its LG3 Subdomain Are Neuroprotective and Acutely Functionally Restorative in Severe Experimental Ischemic Stroke - Ifechukwude Joachim Biose; Ibolya Rutkai; Bryan Clossen; Gary Gage; Kenneth Schechtman; H. Davis Adkisson; Gregory J. Bix (Translational Stroke Research, 2023)
Despite recent therapeutic advancements, ischemic stroke remains a major cause of death and disability. It has been previously demonstrated that ~ 85-kDa recombinant human perlecan domain V (rhPDV) binds to upregulated integrin receptors (α2β1 and α5β1) associated with neuroprotective and functional improvements in various animal models of acute ischemic stroke. Recombinant human perlecan laminin-like globular domain 3 (rhPDV LG3 ), a 21-kDa C-terminal subdomain of rhPDV, has been demonstrated to more avidly bind to the α2β1 integrin receptor than its parent molecule and consequently was postulated to evoke significant neuroprotective and functional effects. To test this hypothesis, fifty male C57Bl/6 J mice studied in a t-MCAO model were randomly allocated to either rhPDV treatment, rhPDV LG3 , or equivalent volume of PBS at the time of reperfusion in a study where all procedures and analyses were conducted blind to treatment. On post-MCAO day 7, 2,3,5-triphenyltetrazolium chloride staining of brain slices was used to quantify infarct volume. We observed that treatment with rhPDV LG3 reduced infarct volume by 65.6% ( p = 0.0001), improved weight loss ( p < 0.05), and improved functional outcome measures ( p < 0.05) when compared to PBS controls, improvements which were generally greater in magnitude than those observed for 2 mg/kg of rhPDV. In addition, treatment with 6 mg/kg of rhPDV LG3 was observed to significantly reduce mortality due to stroke in one model, an outcome not previously observed for rhPDV. Our initial findings suggest that treatment with rhPDV LG3 provides significant improvement in neuroprotective and functional outcomes in experimental stroke models and that further investigation of rhPDV LG3 as a novel neuroprotective therapy for patients with stroke is warranted.